Breasteeding Self Efficacy And Behavior Of Sexio Post Mothers For Breast Milk In Source Living Hospital Ambon - Hitijahubessy, Christy (Pusat Publikasi Nusantara, 2022)
Abstract Caesarean section is an act of delivery assistance through a surgical process that results in changes in tissue continuity and causes pain. The impact that occurs in post-cesarean section patients includes infection in the suture marks, uterine infections, keloids, blood vessel injuries, and amniotic fluid entering the blood vessels. In addition, the discomfort felt by post-sectional patients can cause mother's dependence on nurses and families in meeting the needs of activities and the relationship between mother and baby is disrupted because the mother is more focused on the pain of the surgical wound. In addition, the process of physical and psychological adaptation of the mother will be more severe when the mother undergoes a surgical delivery process. The pain felt by the mother after childbirth and the physical limitations in carrying out activities tend to have the potential to affect the mother's ability to care for her baby and breastfeed her baby. Mother's Milk (ASI) is the best nutrition for babies because it provides adequate nutrition and is in accordance with the baby's needs. The mother's lack of confidence in her ability to breastfeed her baby can be caused by the mother not making initial contact with her baby. This can affect the welfare of the baby in the future. This research is quantitative research. The design used is cross sectional or cross sectional. The sampling technique was done by consecutive sampling. This study aims to analyze the effect of breastfeeding self-efficacy on breastfeeding behavior of post-cesarean mothers. The results of statistical analysis using chy-square showed that breastfeeding self-efficacy for post-cesarean mothers affected poor breastfeeding behavior by 80.9%. On the other hand, mothers who had poor BSE only 31% had good breastfeeding behavior. These results indicate that there is an effect of BSE on the breastfeeding behavior of post-cesarean mothers at the source of life hospital in Ambon (p value = 0.012). There is an influence between breastfeeding self efficacy on the behavior of breastfeeding mothers after cesarean section at Sumber Hidup Hospital in Ambon.